Detection of Incipient Pulp Screen Plugging - Parsa Aryanpour; Robert W. Gooding; James A. Olson (BioResources, 2024)
Aperture plugging is a phenomenon that limits both the capacity and efficiency of pulp screens, which are critical components of the pulping, recycling, and papermaking processes. An understanding of when and how plugs begin to form can help avoid screen plugging, thus increasing papermaking and recycling efficiency. Small scale, fiber-optic pressure sensors were installed within screen cylinder apertures close to where plugging occurs to understand the mechanism of plug formation. Rotor pressure pulses within the aperture were measured during the plugging event. The pulse shape and magnitude during normal operation showed good agreement with past studies in which traditional pressure transducers were installed on the screen cylinder. However, prior to the onset of aperture plugging, the fiber-optic sensors showed that the variability of the pressure pulses increased and pulse magnitude within the slot decreased. The authors demonstrated that combining these variables by quantifying pulse variability using standard deviation and dividing that by pulse magnitude gave a result that was a strong predictor of aperture plugging.